2011
DOI: 10.1590/s1806-37132011000200010
|View full text |Cite
|
Sign up to set email alerts
|

Perfil clínico, epidemiológico e etiológico de pacientes com pneumonia adquirida na comunidade internados em um hospital geral da microrregião de Sumaré, SP

Abstract: Objective: To analyze the clinical, etiological, and epidemiological aspects of community-acquired pneumonia (CAP) in hospitalized individuals. Methods: We prospectively studied 66 patients (> 14 years of age) with CAP admitted to the Hospital Estadual Sumaré, located in the Sumaré microregion of Brazil, between October of 2005 and September of 2007. We collected data related to clinical history, physical examination, pneumonia severity index (PSI) scores, and laboratory tests (blood culture; sputum smear micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 18 publications
(28 reference statements)
0
6
0
1
Order By: Relevance
“…Streptococcus pneumoniae is the most common etiological agent, but the proportion in different studies is variable [Table 4]. [51121–28] Viruses are responsible for CAP in as much as 10–36% of the cases. The widespread antibiotic (mis)use is probably responsible for decreasing culture rates in CAP.…”
Section: Community-acquired Pneumoniamentioning
confidence: 99%
“…Streptococcus pneumoniae is the most common etiological agent, but the proportion in different studies is variable [Table 4]. [51121–28] Viruses are responsible for CAP in as much as 10–36% of the cases. The widespread antibiotic (mis)use is probably responsible for decreasing culture rates in CAP.…”
Section: Community-acquired Pneumoniamentioning
confidence: 99%
“…At least one pathogen was found in 162 patients (72%), the yield being high compared to other similarly conducted studies. [ 8 11 23 24 25 26 27 28 29 30 31 32 33 34 35 ] A comparison of the yield and etiological spectrum in comparison to various international and national studies[ 8 11 23 24 25 26 27 28 29 30 31 32 33 34 35 ] is shown in Tables 5 and 6 , respectively. A higher yield of the pathogens in our study calls for more routine use of these diagnostic modalities for arriving at the etiological diagnosis of CAP.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of a systematic protocol at the hospital under study, including all stages of care to patients with CAP, partially explains this finding. (10,24,26) However, Ewig et al evaluated patients with severe CAP and found that only 11 (61%) of the 18 patients considered to have severe disease were admitted to the ICU. (27) Nevertheless, patients requiring noninvasive ventilatory support the therapeutic regimens recommended for ward patients.…”
Section: Discussionmentioning
confidence: 99%